A Time Modulated Printed Dipole Antenna Array for Beam Steering Application. (16th February 2017) - Gahley, Ruchi; Basu, Banani
Abstract : This paper presents time modulated beam steered antenna array without phase shifters. The beam steering is analyzed considering a two-element time modulated antenna array (TMAA) of printed dipoles with microstrip via-hole balun. The proposed array resonates at the Industrial, Scientific, and Medical (ISM) radio bands, 2.45 GHz and 5.8 GHz, and offers wide bandwidth inherited due to modified structure of ground plane. Array elements are excited by complex exponential excitation signal through broadband power divider and radio frequency (RF) switches to achieve amplitude and phase variation without phase shifters. Differential Evolution algorithm is used to modify the time sequences of the RF switches connected to the antennas to generate radiation pattern with optimum dynamic efficiency by suppressing sideband radiations. Also switch-on time instant of RF switch connected to the subsequent element is modulated to steer the beam towards different directions. The proposed prototype is fabricated followed by parametric optimization. The fabrication results agree significantly well with simulated results.